(untitled) (Research, Society and Development, 2022)
Syphilis remains a public health problem in Brazil and worldwide. Vitória, the capital of Espírito Santo, has reformulated its plan to fight the disease since 2016. Objective: To describe the facilities, difficulties and contributions of the actions developed in the plan to fight syphilis in the city of Vitória (ES), for the four-year period 2016-2019, in the perception of health professionals and managers. Method: An evaluation study for management, with a descriptive character and a qualitative approach. Two focus groups were carried out with 11 managers and 87 semi-structured interviews with health professionals, being 29 doctors, 29 nurses and 29 syphilis references, based on a script that addressed the eight axes of the Vitória vs. Syphilis, with three evaluative questions for each axis. Identical scripts, with 24 evaluative questions, were applied and processed through lexical content analysis. The speeches of the focus group and the interviews were recorded and transcribed literally, using the Voice Noteped Speech to Test application, available at https://dictation.io/speech. The analysis was carried out using the Iramuteq Program, which allowed the organization of the analysis categories. Results: The main facilities were: the availability of rapid test in spontaneous demand and suspected pregnancy; and the availability of prevention supplies. The main difficulties: the insufficiency of human resources (HR) in relation to the demand for work; the lag of pediatricians in the network; and the filling of information by professionals in the electronic medical record. Among the main contributions are: prenatal follow-up with consultations and increase in tests; the reporting of VDRL results by the laboratory for all units; and reducing the spread of the disease. Conclusion: The facilities, difficulties and contributions identified will support managers in defining actions to improve the fight against syphilis.